A new species of Symbiopsocus Li (Psocodea: “Psocoptera”: Psocidae) from Taiwan, China, with a revised checklist and key to species - Liu, Luxi; Li, Fasheng; Liu, Zhiqi (Zootaxa, 2014)
Symbiopsocus yangminus sp. n. is described based on specimens collected from Taiwan, China. We provide an updated checklist and comprehensive geographic distribution of Symbiopsocus, including species from China described in Mecampsis. The genus Symbiopsocus now comprises 20 species from mainland China, two species from Taiwan and one species from Japan. Updated keys to males and females of species from China are provided.